URBANISATION AND UNEVEN DEVELOPMENT OF TOURISM ON THE BRAZILIAN COAST - Fonseca, Maria Aparecida Pontes; Costa, Wagner Fernandes; Fagerlande, Sergio Moraes Rego; Todesco, Carolina (Mercator; Vol 21 (2022), 2022)
The concentration of tourism on the Brazilian coast is widely recognised, despite the fact that its development does not take place in an even manner along the entirety of the coast. As a result, the goal of this article is to examine the spatial diffusion of tourism-related activities on the Brazilian shore and seek to identify the places where it gains more prominence, along with the factors that contributed to its uneven growth. The procedures adopted included the study of tourism-related data as contained in two sources: the Guia Quatro Rodas [‘Quatro Rodas’ Motoring Guide] of the Abril Publishing House and the Brazilian Tourism Map, as published by the Brazilian Department of Tourism in its 2019 edition. The mapping and the analysis of the data allowed us to conclude that the spatial character of coastal tourism was conditioned by the pre-existing urban structure, and concentrated on the major cities. It should be noted that small and mid-sized cities, following specific interventions from the Government, became relevant destinations in the regional, domestic and foreign markets. Keywords : Tourism; Brazilian coastal line; Urbanisation; Uneven Development; Guia Quatro Rodas.